2020
DOI: 10.1017/fmp.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

Moments of Random Multiplicative Functions, I: Low Moments, Better Than Squareroot Cancellation, and Critical Multiplicative Chaos

Abstract: We determine the order of magnitude of E| n≤x f (n)| 2q , where f (n) is a Steinhaus or Rademacher random multiplicative function, and 0 ≤ q ≤ 1. In the Steinhaus case, this is equivalent to determining the order of lim T →∞In particular, we find that E| n≤x f (n)| ≍ √ x/(log log x) 1/4 . This proves a conjecture of Helson that one should have better than squareroot cancellation in the first moment, and disproves counter-conjectures of various other authors. We deduce some consequences for the distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
138
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(144 citation statements)
references
References 29 publications
5
138
1
Order By: Relevance
“…There are also probabilistic and analytic motivations for studying them, see Saksman and Seip's open problems paper [18], for example. The introduction to the previous paper [8] in this sequence contains a more extensive discussion of some of these connections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are also probabilistic and analytic motivations for studying them, see Saksman and Seip's open problems paper [18], for example. The introduction to the previous paper [8] in this sequence contains a more extensive discussion of some of these connections.…”
Section: Introductionmentioning
confidence: 99%
“…Harper [8] showed that for Steinhaus or Rademacher random multiplicative f (n), for all large x we have…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this terminology, we may think of Z N as a sum of random multiplicative functions. A probabilistic approach to problems of computing integral moments, based on this viewpoint, can be found in recent work of Harper [11,13] and Harper, Nikeghbali and Radziwi l l [14]. In many situations, both approaches apply equally well, but sometimes one viewpoint is more illuminating and profitable than the other, and occasionally it is useful to combine them.…”
Section: Introductionmentioning
confidence: 99%